Do Humans Have Souls? Perspectives from Philosophy, Science, and Religion - Murphy, Nancey C. 1951- (2013)
This essay seeks to promote a concept of human nature that is usually called nonreductive physicalism, which is at least not ruled out by Scripture, and may in fact be closer to biblical thinking than dualism. The essay then looks to neuroscience to show that it provides useful insights into how and why we behave as we do.
Keywords: Self-concept; Partitive; Aspective; Trichotomism; Soul; Dualism; Physicalism